Correlation between PDGF-BB and M1-type macrophage in inflammatory bowel disease: a case-control study - Zhiyun Fang; Siwen Qu; Xia Ji; Chuwei Zheng; Juanfen Mo; Jianqiu Xu; Jinming Zhang; Haiyan Shen (BMC Gastroenterology, 2024)
Abstract Background Inflammatory bowel disease (IBD) is a chronic disease in which macrophages play an important role in its pathogenesis. Platelet-derived growth factor-BB (PDGF-BB) secreted by macrophages is involved in the repair of vascular endothelial injury during inflammatory reactions. Methods The expression levels of M1 macrophages and PDGF-BB in serum and colonic mucosa of 30 patients with Crohn’s disease (CD) and 30 patients with ulcerative colitis (UC) were measured using enzyme-linked immunosorbent assays and immunohistochemistry. Logistic regression was used for univariate and multivariate analyses, and receiver operating characteristic curves were used to evaluate diagnostic value. Associations were evaluated using Spearman correlation analysis. Results The expression of serum PDGF-BB and M1 macrophages with positive CXCL9 expression in patients with active-stage IBD [206.55(160.41,262.90)and 337.30(217.73,472.28) pg/ml] was higher than that in patients with remission stage [153.42(107.02,219.68)and 218.37(144.49,347.33)pg/ml] and controls [156.19(91.16,216.08)and 191.20(121.42,311.76)pg/ml](P < 0.05). The expression of PDGF-BB, CD86, and CXCL9 in the colon of patients with active-stage IBD [0.380(0.266,0.542) 0.663(0.480,0.591) and 0.564(0.378,0.765) /µm2] was higher than that in the remission stage [0.308(0.214,0.420), 0.376(0.206,0.591) and 0.413(0.275,0.570) /µm2] and controls [0.265(0.185,0.384), 0.416(0.269,0.534) and 0.497(0.415,0.642) /µm2] (P < 0.05). A positive correlation was observed between CD86 and PDGF-BB, and CXCL9 and PDGF-BB levels in patients with IBD (P < 0.05). CD86 and PDGF-BB in the colonic mucosa were independent risk factors for active IBD, and the area under the curve for their combined diagnosis was 0.754 (95%CI: 0.654–0.852, P < 0.05). Conclusions PDGF-BB was associated with M1 macrophages and has a potential diagnostic value for active IBD. Trial registration Not applicable.